Comparison of different analysis techniques for the determination of muscle onset in individuals with patellofemoral pain syndrome - Kuriki, Heloyse Uliam [UNESP]; de Azevedo, Fabio Micolis [UNESP]; Negrao Filho, Ruben de Faria [UNESP]; Alves, Neri [UNESP] (Elsevier B.V., 2011)
To understand patellofemoral pain syndrome (PFPS), recent studies have focused on assessing the onset in the vastus medialis and vastus lateralis to determine whether there is a delay between these muscles' activation. However, the results of these studies are not in agreement, as some research shows that there is a delay in the VMO, while others do not show delay. It has been suggested that this discrepancies may be due to differences in the signal processing and analysis. For this reason, this study aimed to compare the three techniques used for onset determination - automatic detection, visual inspection and cross-correlation -and to verify whether these methods are able to detect PFPS. The surface electromyography evaluation procedure was conducted in 22 pain-free control individuals and 11 with PFPS diagnoses, during a stair climbing. The standard error of measurement (SEM) showed that cross-correlation presents the lower variation (2.56/3.27, control/PFPS) in relation to visual (3.77/10.19, control/PFPS) and automatic detection (43.23/51.98, control/PFPS, respectively). But when using the cross-correlation technique, we were not able to distinguish the groups (-6.56/-9.74 ms, control/PFPS, p = 0.15). Therefore, use of muscle onset may not be the best way to distinguish individuals with PFPS. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Patellofemoral pain syndrome; Electromyography analysis techniques; Onset